2009
DOI: 10.1080/10550490802408936
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Trial: Double‐Blind Comparison of Nefazodone, Bupropion‐SR, and Placebo in the Treatment of Cannabis Dependence

Abstract: The present study investigated the efficacy of nefazodone and bupropion-sustained release for treating cannabis dependence. A double blind, placebo controlled, piggy back design was employed to assess if nefazodone and bupropion-sustained release increased the probability of abstinence from cannabis and reduced the severity of cannabis dependence and cannabis withdrawal symptoms during a 13-week outpatient treatment program. One-hundred and six participants (M=32 years; Females n=25) were randomized to one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 50 publications
(55 reference statements)
4
81
0
Order By: Relevance
“…This limited the extent of analysis that was possible.The medications investigated, grouped according to type and mechanism of action, were: preparations containing THC, dronabinol (Levin 2011) and nabiximols (Allsop 2014);selective serotonin reuptake inhibitor (SSRI) antidepressants fluoxetine (Cornelius 2010), escitalopram (Weinstein 2014);mixed action antidepressants (noradrenergic and serotonergic effects), nefazodone (Carpenter 2009), mirtazapine (Frewen 2007), venlafaxine (Levin 2013);anticonvulsant and mood stabilisers divalproex sodium (Levin 2004), gabapentin (Mason 2012), lithium (Johnston 2012);atypical antidepressant (dopamine reuptake inhibitor and weak norepinephrine reuptake inhibitor) bupropion (Carpenter 2009; Penetar 2012);anxiolytic (serotonin 5-HT 1A partial agonist) buspirone (McRae-Clark 2009);selective norepinephrine reuptake inhibitor atomoxetine (McRae-Clark 2010);a supplement promoting glutamate release and modulating N-methyl-D-aspartate (NMDA) receptor, N-acetylcysteine (Gray 2012). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This limited the extent of analysis that was possible.The medications investigated, grouped according to type and mechanism of action, were: preparations containing THC, dronabinol (Levin 2011) and nabiximols (Allsop 2014);selective serotonin reuptake inhibitor (SSRI) antidepressants fluoxetine (Cornelius 2010), escitalopram (Weinstein 2014);mixed action antidepressants (noradrenergic and serotonergic effects), nefazodone (Carpenter 2009), mirtazapine (Frewen 2007), venlafaxine (Levin 2013);anticonvulsant and mood stabilisers divalproex sodium (Levin 2004), gabapentin (Mason 2012), lithium (Johnston 2012);atypical antidepressant (dopamine reuptake inhibitor and weak norepinephrine reuptake inhibitor) bupropion (Carpenter 2009; Penetar 2012);anxiolytic (serotonin 5-HT 1A partial agonist) buspirone (McRae-Clark 2009);selective norepinephrine reuptake inhibitor atomoxetine (McRae-Clark 2010);a supplement promoting glutamate release and modulating N-methyl-D-aspartate (NMDA) receptor, N-acetylcysteine (Gray 2012). …”
Section: Resultsmentioning
confidence: 99%
“…mixed action antidepressants (noradrenergic and serotonergic effects), nefazodone (Carpenter 2009), mirtazapine (Frewen 2007), venlafaxine (Levin 2013);…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there is no conclusive way to objectively verify abstinence from cannabis for the previous 24 h, because THC has metabolites that can last for a week or more beyond last use. However, a number of reports suggest a strong concordance between urine toxicology and self-reported drug use (Carpenter et al 2009;Carroll et al 1994;Martin et al 1988), suggesting that, when elicited in a research setting in a nonjudgmental fashion, self-reported drug use is accurate.…”
Section: Subjectsmentioning
confidence: 94%
“…Most studies thus far have had negative, discouraging, or mixed results. Studies of bupropion (Carpenter, McDowell, Brooks, Cheng, & Levin, 2009), divalproex (Levin et al, 2004), mirtazapine (Haney et al, 2010), nefazodone (Carpenter et al, 2009), and dronabinol (oral THC) (Levin et al, 2011) have been generally disappointing. There is some question in the latter study about whether the dosing of dronabinol was adequate at 20 mg twice a day, as it reduced withdrawal symptoms but did not yield a reduction in marijuana use when compared to placebo treatment.…”
Section: Is There a Role For Pharmacotherapy?mentioning
confidence: 99%